Technology in Schools - Ackerman, Gary L (Open textbook library., 2022)
My purpose in writing this book is to give readers a view into the work of managing information technology in schools. IT professionals will notice differences (some nuanced and some significant) between the needs and expectations of IT users in business and IT in school. With the more complete and more accurate concept the nature of the computing environment necessary for successful schooling, which I intend to provide through this book, IT professionals will be better prepared to meet those needs. Educators will also benefit from this book by clarifying the nature of their IT needs and how these may be different from those that are familiar to IT professionals who are hired to work in your school.